Dynamics Of Environmentally Conscious Marine Tourism Development Through Collaborative Governance Models In Simeulue - Macella, Agatha Debby Reiza; Juraida, Irma; Safrida, Safrida; Rahmadani, Saumi; Saputri, Ima Wahyuni (JURNAL TRIAS POLITIKA, 2025)
Simeulue has 10 marine tourism destinations that are prioritized for development. Unfortunately, no tourism awareness groups have been formed to help develop marine tourism, even though almost every village has marine tourism potential. This research aims to examine more deeply the conditions of collaboration between the government and other sectors in the Development of Environmentally Sound Marine Tourism in Simeulue Regency. This research method uses a descriptive qualitative approach and use Taxonomy analysisthing. The result of this research is that this collaboration is reflected in the formulation of the tourism development policy of Siemulue Regency in the Regional Tourism Development Master Plan (RIPPARKAB). However, there are obstacles in this collaboration, namely conflicts over the transfer of land from the community to the government to be developed, especially in the Pinang Island destination. Before the collaboration was established, there was potential and openness from the government to involve participation from other sectors. Then the collaboration process began with a face-to-face dialog that formed the commitment of each party. Furthermore, there was friction in the collaboration, namely the existence of the Pinang Island coastal land conflict, limited understanding and environmental preservation around Pinang Island marine tourism, then ended in the temporary result of collaboration, namely RIPPARKAB as a joint commitment in supporting the development of environmentally sound marine tourism.